2014
DOI: 10.1002/ep.11927
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative degradation of lurgi coal gasification wastewater: Optimization using response surface methodology

Abstract: Lurgi coal‐gasification wastewater with an initial total organic carbon (TOC) of 5000 mg/L and ammonia nitrogen (NH3N) of 1500 mg/L was treated by supercritical water oxidation technology to make the effluent reach the national wastewater discharge standard I in China (TOC < 20 mg/L, NH3N < 15 mg/L). Response surface methodology method combined with central composite design and regression analysis were used to statistically analyze and optimize the operating parameters. The effect degree of the parameters on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The results indicated that both modified kapok had higher adsorption capacity of 23.4 and 34.6 mg/g than unodifiedc (4.70 mg/g). Also, Langmuir isotherm was adequately described the sorption data at which Adsorption capacity decreased with a decrease in the pH (Wang et al, 2014g).…”
Section: Carbonized Eupatorium Adenophorum Andmentioning
confidence: 82%
See 1 more Smart Citation
“…The results indicated that both modified kapok had higher adsorption capacity of 23.4 and 34.6 mg/g than unodifiedc (4.70 mg/g). Also, Langmuir isotherm was adequately described the sorption data at which Adsorption capacity decreased with a decrease in the pH (Wang et al, 2014g).…”
Section: Carbonized Eupatorium Adenophorum Andmentioning
confidence: 82%
“…were found to be 0.161 g volatile suspended solid (VSS)/g chemical oxygen demand (COD), 0.039 1/d, respectively, whereas for first-order model (K -1 ) was 4.56 1/d. Wang et al, (2014g) (2014d) studied the potential use of zero valent iron (ZVI) biochar composite (BBCF) to remove and reclaim Ag + ions from aqueous. BBCF was showed to exhibit 28 nm particle size.…”
Section: Chemical Wastewatermentioning
confidence: 99%
“…With the maximum H 2 yield and the minimum yield of tar and char as constraints, the optimal operating parameters were 550 • C, 24.99 MPa, 851.28 s, and OC = 0.31. Wang et al [96] applied RSM combined with central composite design and regression analysis to optimize the operating parameters for the oxidation process of Lurgi coal-gasification wastewater in SCW. With TOC and NH3-N degradation rate as response variables and temperature, OR, pressure and residence time as explanatory variables, a regression model was then established, which showed the order for the effect degree of the parameters on the TOC and the NH 3 -N degradation rate: temperature > oxygen ratio > reaction time > pressure.…”
Section: Multiple Nonlinear Regression Methodsmentioning
confidence: 99%
“…As an economic and efficient treatment technology, biological treatment process has a growing concern, and treatment process enrichment, biodegradation improvement, pollutants removal, and sludge production reduction are the key issues for the technological innovation of biological treatment. Besides, the selection and optimization for advanced oxidation processes (cavitation, photocatalytic oxidation, and Fenton's chemistry) and chemical oxidation (ultilization of ozone and hydrogen peroxide) is widely investigated to degrade toxic and biorefreactory chemical constituents, etc. In comparison with advanced oxidation processes, chemical oxidation can yield high phenol's removal efficiency without secondary pollution, but high operation costs and low NH 3 N removal limits its application .…”
Section: Introductionmentioning
confidence: 99%